The role of strategic management in developing the administrative competence of employees in Islamic banks in Tulkarm Governorate - Hejazi, Mahmoud Hasan (Journal of Economic, Administrative and Legal Sciences, 2024)
The study aimed to identify the role of strategic management in developing the administrative competence of employees in Islamic banks in Tulkarm Governorate according to the areas (formulation of strategic plans, implementation and application of strategic management, and evaluation of strategic management), and to achieve the goal of the study, the descriptive analytical correlative approach was used. A questionnaire was developed and consisted of (30) items, and the study population consisted of Islamic banks employees in Tulkarm Governorate, where their number reached (50) employees. and an employee, and a sample of (30) male and female employees was selected, This study was conducted in 2023, as one of the most important results of the study was the existence of a direct correlation between the role of strategic management and the development of the administrative competence of employees. The study made several recommendations, the most important of which were: Activating the participation of employees in Islamic banks in the process of developing strategic plans because of its positive benefits on performance and raising morale, which leads to an increase in administrative efficiency, as well as urging Islamic banks to seek to increase and intensify training courses in the field of implementing and applying strategic management based on functional needs and in accordance with a clearly defined strategic plan.